Periodic Structure in the Megaparsec-Scale Jet of PKS 0637-752 - Godfrey, Leith; Lovell, J.; Burke-Spolaor, S.; Ekers, Ronald; Bicknell, G.; Birkinshaw, M.; Worrall, D.; Jauncey, D.; Schwartz, D.; Marshall, H.; Gelbord, J.; Perlman, E.; et al. (Institute of Physics Publishing Ltd., 2012)
We present 18 GHz Australia Telescope Compact Array imaging of themegaparsec-scale quasar jet PKS 0637-752with angular resolution ~0.58.We draw attention to a spectacular train of quasi-periodic knots along the inner 11of the jet, with average separation ~1.1 arcsec (7.6 kpc projected). We consider two classes of model to explainthe periodic knots: those that involve a static pattern through which the jet plasma travels (e.g., stationary shocks)and those that involve modulation of the jet engine. Interpreting the knots as re-confinement shocks implies thejet kinetic power Qjet ~ 1046 erg s-1, but the constant knot separation along the jet is not expected in a realisticexternal density profile. For models involving modulation of the jet engine, we find that the required modulationperiod is 2×103 yr < t < 3×105 yr. The lower end of this range is applicable if the jet remains highly relativisticon kiloparsec scales, as implied by the IC/CMB model of jet X-ray emission. We suggest that the periodic jetstructure in PKS 0637-752 may be analogous to the quasi-periodic jet modulation seen in the microquasar GRS1915+105, believed to result from limit cycle behavior in an unstable accretion disk. If variations in the accretionrate are driven by a binary black hole, the predicted orbital radius is 0.7 pc a 30 pc, which corresponds to amaximum angular separation of ~0.1–5 mas.